Nanoscale ceramic plasmonic catalysts for stabilizing and assisting plasma combustion
By combining the thermoelectric effect and field-enhanced emission technology of nano-scale ferroelectric bodies in plasma catalysts, the plasma catalyst in the form of ceramic-matrix nanocomposites is solved in the prior art, and the plasma facilities are difficult to scale and self-powered in the prior art. , realizes self-powered and efficient plasma-assisted combustion effects.
Patent Information
- Application Number
- CN202080098875.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-24
AI Technical Summary
The existing plasma generation facilities are difficult to scale their capacity and size, and cannot supply self-power, and cannot effectively use the combustion thermal energy to convert electricity. They only use the catalytic properties of the plasma and fail to exert their synergistic effects and energy transmission.
Using a plasma catalyst in the form of ceramic-matrix nanocomposite, combined with the thermoelectric effect, Schottky effect and field-enhanced emission of nano-scale ferroelectric bodies, thermal energy is obtained through UV-VIS-IR irradiation and converted into VUV-soft X-rays Ionizing radiation, used for self-powered plasma catalysts, forms self-organized nanoporous wafers and crystalline nanowhiskers.
Realizes self-powered plasma catalysts, which can operate stably at temperatures of hundreds of degrees Celsius, provide a scalable structure, with inherent reliability and direct VUV-soft X-ray generation capabilities, and enhances plasma-assisted combustion in the combustion chamber Effect.
Smart Images

Figure CN115335144B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to plasma catalysts for stimulating and sustaining plasma-assisted combustion, including novel plasma catalyst configurations in the form of so-called ceramic-matrix nanocomposites, and discloses novel combinations of valve metal oxides, polar transition metal oxides, rare earth oxides and phosphides, alkali metal oxides, silicon oxides, silicon carbides and nitrides, including ternary and higher-order composites. Background Technology
[0002] The catalytic properties of low-temperature partially ionized plasma (LTP) for the synthesis and reforming of materials, waste treatment, etc., are well established and have provided a permissible technology for industrial use. Typically, in LTP, or so-called nonthermal plasma, the ion pair number is 10-1. 9 -10 13 cm -3 Electron temperature ≤10 5 K. LTP is a non-equilibrium plasma, where the electron temperature is much higher than that of ions and neutral particles.
[0003] LTP is generated using conventional LTP generation facilities based on discharge, laser irradiation, ultra-high frequency to extra-high frequency radiation, relativistic electron beams, or radio-ionization techniques.
[0004] The main drawback of the prior art is that plasma generation facilities are electromechanical and / or opto-electromechanical devices with complex feedthroughs for energy-forming plasma introduction and external high-power sources, rather than being self-powered. In other words, they cannot obtain, for example, the thermal energy of combustion in the form of ultraviolet-visible-infrared (UV-VIS-IR) irradiation bands, thermoelectrically generate electricity, and convert the electricity into vacuum ultraviolet-soft X-ray (VUV-soft X-ray) ionizing radiation bands as plasma-forming media through internal field-enhanced emission and electron scattering.
[0005] A drawback of existing technologies is the difficulty in scaling up plasma generation facilities for reactors of various capacities and sizes.
[0006] The drawbacks are related to limited functionality because it only utilizes the catalytic properties of plasma, rather than the synergistic effects and catalytic properties of the surface from which energy can be transferred and / or separated to form plasma.
[0007] Representative examples of prior art can be found in the following documents: US7592564B2 – Plasma generation and processing with multiple radiation sources; US7608798B2 – Plasma catalyst; US2019321799A1 – Dielectric barrier discharge reactor for catalytic nonthermal plasma production of hydrogen from methane; KR20190092939A – Plasma-Photo Catalyst Reactor for Removal of Ammonia Packing Material coated with Photo Catalyst for the same Reactor and Preparation of the same Packing. Material); CN109999817A–Cu / ZnO-ZrO2 solid solution catalyst and glow discharge plasma assisted preparation method and application thereof; KR20180116952A–Plasma and catalyst type dry reforming apparatus and method;WO2009116868A1 – Process for the use of alkali metal or alkaline earth metal containing organic materials and composites in the microwave-assisted plasma decomposition of said compounds for the production of syngas; CN108895482A – Combustion flamestabilizer assisted by discharging plasma.
[0008] European patent application EP3280230A1 (Efenco) (Published on 07.02.2018) relates to a method and apparatus for generating plasma in a heat carrier to stabilize combustion and neutralize toxic products. The object of the invention is to generate a so-called synchrotron radiation beam with suitable parameters and sufficient power and a suitable spectral composition, which will be used as a finely configurable tool for the selective ionization of combustion products, i.e., the hot combustion gases that form the heat carrier. Summary of the Invention
[0009] The purpose of this invention is to produce a plasma catalyst, which is a synergistic combination of plasma and solid catalyst, whose electrophysical interactions with each other (as an additional enhancing factor), and is embodied in the form of a nanocomposite material for lining the combustion chamber walls, and is intended to initiate and sustain plasma-assisted combustion.
[0010] In the context of this invention, the IUPAC groups in the periodic table and the chemical elements within the corresponding IUPAC groups mentioned in the specification and claims refer to the groups with the modern standard names adopted by IUPAC in 1990. The latest IUPAC periodic table was published on December 1, 2018.
[0011] Valve metals are a group of inner transition metals in the periodic table that exhibit valve-like properties. This can be defined as follows: when acting as a cathode, these metals allow current to pass through, but when acting as an anode, they impede current flow due to the rapid formation of an insulating anodic film. Because of this property, they are called valve metals. They include:
[0012] -IUPAC Group 4: Group 4 consists of a group (column) of chemical elements in the periodic table, including titanium (Ti), zirconium (Zr), and hafnium (Hf);
[0013] -IUPAC Group 5: Group 5 consists of a group (column) of chemical elements in the periodic table, including vanadium (V), niobium (Nb), and tantalum (Ta);
[0014] -IUPAC Group 6: Group 6 consists of a group (column) of chemical elements in the periodic table, including tungsten (W);
[0015] - IUPAC Group 13: Group 13 is a group (column) of chemical elements in the periodic table, including aluminum (Al).
[0016] In the context of this invention, the IUPAC group of the periodic table and the chemical elements in the corresponding IUPAC group are used:
[0017] - IUPAC Group 1: Group 1 (alkali metals) consists of a group (column) of chemical elements in the periodic table, including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr);
[0018] -IUPAC Group 2: Group 2 (alkaline earth metals) is a group (column) of chemical elements in the periodic table, including beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba);
[0019] -IUPAC Group 3: Group 3 consists of a group (column) of chemical elements in the periodic table, including the lanthanides;
[0020] -IUPAC Group 4: Group 4 consists of a group (column) of chemical elements in the periodic table, including titanium (Ti), zirconium (Zr), and hafnium (Hf);
[0021] -IUPAC Group 5: Group 5 consists of a group (column) of chemical elements in the periodic table, including vanadium (V), niobium (Nb), and tantalum (Ta);
[0022] - IUPAC Group 6: Group 6 consists of a group (column) of chemical elements in the periodic table, including chromium (Cr), molybdenum (Mo), and tungsten (W);
[0023] -IUPAC Group 8: Group 8 consists of a group (column) of chemical elements in the periodic table, including iron (Fe);
[0024] - IUPAC Group 10: Group 10 consists of a group (column) of chemical elements in the periodic table, including nickel (Ni), palladium (Pd), and platinum (Pt);
[0025] - IUPAC Group 11: Group 11 consists of a group (column) of chemical elements in the periodic table, including copper (Cu), silver (Ag), and gold (Au);
[0026] - IUPAC Group 12: Group 12 consists of a group (column) of chemical elements in the periodic table, including zinc (Zn);
[0027] - IUPAC Group 13: Group 13 consists of a group (column) of chemical elements in the periodic table, including boron (B), aluminum (Al), gallium (Ga) and indium (In).
[0028] - IUPAC Group 14: Group 14 consists of a group (column) of chemical elements in the periodic table, including carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb);
[0029] - IUPAC Group 15: Group 15 consists of a group (column) of chemical elements in the periodic table, including nitrogen (N), phosphorus (P), arsenic (As), antimony (Sb), and bismuth (Bi);
[0030] - IUPAC Group 16: Group 16 is a group (column) of chemical elements in the periodic table, including oxygen (O), sulfur (S) and selenium (Se).
[0031] The plasma catalyst (hereinafter referred to as plasma catalyst) of the present invention, in the form of a ceramic-matrix nanocomposite material, combines several physical effects, the main effects being: thermoelectric effect in nanoscale ferroelectrics, Schottky effect, field-enhanced emission and electron scattering to the film, ionization of beams of free electrons and photons, spontaneous positive feedback between related processes; and the catalytic activity of the material used.
[0032] According to the present invention, the plasma catalyst obtains thermal energy through combustion in the form of ultraviolet-visible-infrared (UV-VIS-IR) irradiation bands, generates electricity thermoelectrically, and converts the electricity into vacuum ultraviolet-soft X-ray (VUV-soft X-ray) ionizing radiation bands as plasma forming media through internal field-enhanced emission and electron scattering.
[0033] Energy harvesting (also known as energy extraction) is the conversion of ambient energy released during combustion, for example in the environment (e.g., in a combustion chamber), into electrical energy for use in powering autonomous electronic devices or circuits, and in the context of this invention, for use in powering a plasma catalyst according to the invention.
[0034] The plasma catalyst according to the invention is the lining of the combustion chamber, and therefore, the energy for plasma formation is directly introduced into the combustion chamber. The plasma catalyst operates under conditions of several hundred degrees Celsius and a weakly oxidizing and alkaline environment.
[0035] The plasma catalyst comprises several functional layers of nanoscale materials, the main layers of which are: layers that absorb incident UV-VIS-IR and convert it into VUV-soft X-ray output, including crystalline (polycrystalline or polycrystalline structure) and / or single-crystal (single-crystal structure) nanowhiskers; nanoporous wafers as a matrix for depositing nanowhiskers; and in the absence of a specific wafer coating, the wafer material itself acts as a solid catalyst.
[0036] Preferably, the nanoscale material is a valve metal oxide, a polar transition metal oxide, a rare earth oxide and phosphide, an alkali metal oxide and nitride, a silicon oxide, a silicon carbide and nitride, including ternary and higher-order complexes, which are combined and synthesized in a defined manner (by chemical formula) according to their functional properties and purposes.
[0037] Preferably, the absorption and conversion layer is an array of vertically arranged perovskite-like polycrystalline and / or single-crystal nanowhiskers (hereinafter referred to as nanowhiskers), with or without an additional coating, and deposited within the pores of the wafer. Nanowhiskers are defined as one-dimensional (1D) nanocrystal structures with a diameter of 1 to 100 nm and an aspect ratio (length to diameter) exceeding 100.
[0038] Preferably, the nanoporous wafer is a planar parallel plate comprising an array of self-organized, honeycomb-like, and nearly monodisperse nanopores, open on both sides or only one side and oriented perpendicular to the upper / bottom surface of the wafer. The wafer size is scalable and depends on the dimensions of the liner and combustion chamber.
[0039] The plasma catalyst according to the invention is a sintered solid thin ceramic brick used for lining the combustion chamber walls. The wall lining can act as an additional barrier against heat, oxidation, and alkalinity.
[0040] The plasma catalyst according to the invention has a scalable structure; it has no moving parts, is self-powered, and is inherently reliable.
[0041] The present invention is generally classified as a plasma catalyst with a thermally driven direct VUV-soft X-ray generation device, and is therefore not limited to the above-mentioned thermal energy sources.
[0042] According to the present invention, a plasma catalyst in the form of a ceramic-matrix nanocomposite material is provided, the nanocomposite material comprising at least a first part and a second part, wherein the first part comprises a nanoporous wafer and the second part comprises crystalline nanowhiskers.
[0043] In the plasma catalyst, the nanoporous wafer comprises at least one of valve metal oxides, silicon / silicon dioxide, and silicon carbide from groups 4, 5, 6, and 13 of the periodic table IUPAC.
[0044] The nanowhiskers include at least one of the following: perovskite-like polycrystalline and / or single-crystal ferroelectrics with thermoelectric properties, transition metals, conductive metal-oxide-metal ceramics, or composites thereof.
[0045] In a preferred embodiment, the first and second portions are covered by a top cover in the form of a multilayer film or wafer.
[0046] Preferably, the top cover comprises at least three layers:
[0047] -Catalyst grid;
[0048] - A layer to prevent oxidation and alkalinity; and
[0049] - Transparent conductive oxide ceramic layer.
[0050] In another preferred embodiment of the plasma catalyst, the nanocomposite material is in the form of a sintered solid thin ceramic brick.
[0051] In another preferred embodiment of the plasma catalyst, the nanoporous wafer of the first part is in the form of a planar parallel wafer, comprising an array of self-organized, honeycomb-like and almost monodisperse cylindrical or V-shaped pores that open on both sides or only one side and are oriented perpendicular to the upper / bottom surface of the wafer.
[0052] In another preferred embodiment of the plasma catalyst, the nanoporous wafer is ceramic, synthesized according to the following formula:
[0053] (Me 4 ) I (Me 5 ) J (Me 6 ) K (Me 13 ) L (Si) M (SiC) N (O) Z ,
[0054] Among them Me 4 It is a valve metal of Group 4 transition metals in the IUPAC periodic table.
[0055] Among them Me 5 It is the valve metal of Group 5 transition metals in the IUPAC periodic table.
[0056] Among them Me6 It is the valve metal of Group 6 transition metals in the IUPAC periodic table.
[0057] Among them Me 13 It is the valve metal of the IUPAC group 13 transition metals in the periodic table, and
[0058] The indices I, J, K, L, M, and Z represent the numerical proportions of each type of atom; and one of I, J, K, L, M, and Z is greater than 0, otherwise N = 1.
[0059] In another preferred embodiment of the plasma catalyst, the thermoelectric ferroelectric material is a perovskite-like crystalline nanocrystal, in polycrystalline or single-crystal form, synthesized according to the following formula:
[0060] ∑[(Me 1-2 ) I (Me 1-2 ) J ](Me 3 ) K ∑[(Me 4-6 ) L (Me 4-6,8 ) M ]∑[(Me 4-6 ) N (Me 12-15 ) R ](sMe 13-16 ) X (nMe 14-16 ) Y (O) Z ,
[0061] The superscript index represents the IUPAC group of the periodic table;
[0062] The subscript exponents I, J, K, L, M, N, R, X, Y, and Z represent the numerical proportion of each type of atom;
[0063] Where ∑[…] represents the formation of a complex of several elements from one or more groups including the superscript index; and
[0064] Where Me, sMe, and nMe represent metal, metalloid, and nonmetal, respectively; and
[0065] At least one of I, J, L, Z is greater than 0, and usually 0≤I, J, K, L, M, N, R, X, Y, Z≤30.
[0066] The invention also includes the use of plasma catalysts as a component of a combustion chamber lining, which acts as an additional barrier against heat, oxidation, and alkalinity to the combustion chamber walls.
[0067] Preferably, the combustion lining acts as an additional barrier against heat, oxidation, and alkalinity to the combustion chamber walls.
[0068] Further applicable areas will become apparent from the description provided herein. The descriptions and specific embodiments in this summary are intended for illustrative purposes only and are not intended to limit the scope of this disclosure. Attached Figure Description
[0069] The accompanying drawings described herein are for illustrative purposes only, and not for all possible implementations, and are not intended to limit the scope of this disclosure, and wherein:
[0070] Figure 1 An outline of the disclosed implementation methods is described;
[0071] Figure 2 This illustrates the size-driven effect in nanoscale ferroelectric perovskites;
[0072] Figure 3 This explains the electrophysical phenomenon;
[0073] Figure 4 This illustrates the synergistic effect in plasma catalysis;
[0074] Figure 5 This illustrates the interaction between the plasma catalyst, LTP, and solid catalyst;
[0075] Figure 6 The overall structural concept of plasma catalyst and ceramic-matrix nanocomposite material is explained;
[0076] Figure 7 The structure and materials of nanoporous wafers are described.
[0077] Figure 8 It explains the nanocrystals, their structure, and materials;
[0078] Figure 9 The description of the top cover, its structure, and materials is explained;
[0079] Figure 10 This illustrates the wafer bonding technology for plasma catalysts.
[0080] One or more ways of implementing the present invention
[0081] The present invention has been described and illustrated in detail with reference to the accompanying drawings. However, the present invention is not limited to the embodiments described above or in the drawings. Other possible embodiments and combinations of typical features may exist that can be derived and implemented according to this specification and the appended claims.
[0082] This document discloses at least one exemplary embodiment of the present invention. It should be understood that modifications, substitutions, and alternatives will be apparent to those skilled in the art and can be made without departing from the spirit and scope of the invention. This description is intended to cover any apparatus or variation of one or more exemplary embodiments. Furthermore, in this specification, the terms "comprise," "comprising," "include," or "including" do not exclude other elements or steps, the terms "one" or "single" do not exclude a plural, and the term "and / or" means either one or both. Additionally, the features or steps already described may be used in combination with other features or steps and in any order, unless the description or context otherwise suggests.
[0083] To better understand the purpose of this invention and its implementation, an explanation of the physical effects and phenomena on which this invention is based is first given.
[0084] Thermoelectric properties of nanoscale ferroelectrics
[0085] When the dimensions of ferroelectric perovskites are effectively restricted to the 0-2D nanoscale, the laws governing the bulk ferroelectric properties no longer apply. Based on the phenomenological theory and computational model of the Landau-Ginzburg-Devonshire system, the polarization (thermoelectric coefficient) and phase transition temperature in the ferroelectric nanostructure can be fine-tuned using dimensionality effects, thus providing the system with a tunable, large thermoelectric response.
[0086] Variations in the electrophysical, optical, and mechanical properties of 0-2D ferroelectrics are related to changes in surface tension, which induces internal pressure in the radial direction. Internal pressure in 0-2D nanostructures increases with decreasing size; for example, in 1D cylindrical crystals in the form of nanowhiskers, it increases with radius rather than aspect ratio. The effect of pressure depends on the direction of polarization relative to the crystal axis.
[0087] Figure 2 A family of curves depicting the size-driven effect of nanowhiskers. Figure 2 In the diagram, a) and b) indicate the Curie temperature T of various ferroelectrics. C The typical correlation between the thermoelectric coefficient P (polarization) and the radius R of cylindrical nanocrystals, where T C It is the temperature at which the ferroelectric phase transitions to the paraelectric second-order phase. When the polarization vector is oriented along the axis, T... C The thermoelectric coefficient P (polarization) varies with radius (up to the critical radius R). CR The decrease in long-range interactions (which favor ferroelectricity at the critical radius) is followed by an increase, while for polarization perpendicular to the axis, T... CBoth P and P decrease as the radius decreases.
[0088] Field Enhanced Launch
[0089] Figure 3 Section a) reveals the conditions for field emission and field-enhanced emission of electrons. Typically, for field emission, an intensity E ~ 10 is present on the emission surface. 7 An electric field of V / cm (1V / nm) is a necessary condition for electron tunneling through the surface barrier.
[0090] In fact, in a planar parallel electrode system, a strength of 10 is obtained. 7 A uniform electric field of V / cm is impossible. An exception is when a non-uniform field is generated due to variations in the shape of the emitting surface (e.g., using nanoscale cylinders, cones, etc.). Therefore, the field strength of the emitter-anode system can be increased by E = γ·U, where U is the voltage applied to the emitting surface and γ (1 / cm) is the field enhancement factor.
[0091] Figure 3 Figure b) shows the correlation between the field enhancement factor γ(d,D) of the coaxial cylindrical system and the diameter d and the distance D between the emitting surface and the anode. As can be seen from the figure, if the field enhancement factor is within 2.3 x 10⁻⁶... 4 cm -1 ≤γ≤2.6x10 6 cm -1 If the voltage applied to the emitting surface within the range is 4V≤U≤450V, then the electric field strength becomes E≥10. 7 V / cm is a necessary condition for field-enhanced emission of electrons.
[0092] Electron scattering to the membrane
[0093] Figure 3 Schematic diagrams c) and d) illustrate the difference between electron scattering in solids and multilayer films. Electrons scattered into multilayer films exhibit more complex phenomena, not only due to the different materials of the layers, but also due to scattering at the inner interlayer boundaries (Bragg's effect) and interlayer exchange interactions.
[0094] In the case of solids, the electron penetration depth (electron track length) R into the material KO It can be estimated using the Kanaya–Okayama expression as follows:
[0095] R KO =(0.0276·A·E0) 1.67 ) / ρ·Z 0.89 ,
[0096] Where A is the atomic mass; E0 is the initial electron energy; ρ is the matter density; and Z is the atomic number. In the case of compounds (by simplifying the assumption, multilayer films can be treated as compounds), the average values are substituted into the calculation.
[0097] The depth at which X-rays are produced can be estimated using the Anderson-Hasler expression:
[0098] R AH =0.064(E0) 1.68 –E C 1.68 ) / ρ,
[0099] Where E C It is the absorption edge (critical excitation) energy.
[0100] Typically, the electronic path is calculated using mathematical modeling techniques based on Monte Carlo simulations.
[0101] Synergistic effect of plasma and heterogeneous catalysts
[0102] Figure 4 Experimental data graphs are plotted to assess the effectiveness of various catalytic techniques in the destruction of toluene. When the catalytic properties of the discharge plasma are combined with a solid catalyst placed in a chemical reactor, the relative efficiency (product yield) during the destruction of toluene reaches a maximum of 65%.
[0103] Figure 5 The interaction mechanisms in the plasma catalyst-LTP-solid catalyst system are illustrated. The following types of interactions exist: ionizing radiation–matter; plasma–surface; combined plasma radiation–environment; and matter–heterogeneous catalyst.
[0104] VUV-soft X-ray ionizing radiation effectively generates reactive radical fragments as well as vibrationally and electronically excited matter. These chemically active substances drive reaction kinetics and pathways, producing unique structures in the gas phase that cannot be obtained otherwise, at least not in a cost-effective manner.
[0105] The boundaries surrounding the plasma generate strong gradients, within which the plasma's properties change dramatically. In these boundary regions, the incident VUV-soft X-ray radiation interacts most strongly with the plasma, often evoking unique responses. Furthermore, precisely at the boundary surfaces, complex interactions occur between the plasma and the surface.
[0106] Photons generated by the recombination of excited matter in the plasma interact with other matter in the plasma or the plasma boundary, and they can exit the plasma in the form of UV-VIS-IR irradiance.
[0107] Basically, three reaction mechanisms have been proposed for the redox reactions on the surface of solid catalysts:
[0108] The Langmuir–Hinshelwood mechanism (LH) involves two molecules being adsorbed at adjacent sites, and the adsorbed molecules undergoing a bimolecular reaction.
[0109] The Eley–Rideal mechanism (ER) posits that only one type of molecule is adsorbed on the catalyst surface, while another reacts directly with it from the gas phase without adsorption; and
[0110] The Mars and Van Krevelen (MvK) mechanism posits that some of the reaction products leave the surface of the solid catalyst, carrying one or more components of the catalyst lattice.
[0111] According to the present invention, the plasma catalyst is in the form of a UV-VIS-IR irradiation band to obtain thermal energy through combustion, and generates electricity thermoelectrically. The electricity is converted into VUV-soft X-ray ionizing radiation band as a plasma forming medium through internal field enhancement emission and electron scattering.
[0112] The plasma catalyst according to the invention is embodied as a ceramic-matrix nanocomposite material based on a combination of valve metal oxides, polar transition metal oxides, rare earth oxides and / or phosphides, alkali metal oxides, silicon and / or silicon oxides, silicon carbides and / or nitrides, including ternary and higher-order composites, in the form of at least one wafer with or without an additional coating.
[0113] Figure 6 The design of one possible implementation of a freely expandable structure for a plasma catalyst is described. The plasma catalyst is a composite material comprising at least one wafer (602) having an array of self-organized, honeycomb-like, and nearly monodisperse pores (603), wherein each pore contains at least one of three nanowhiskers (604) or (605) or (606). Possibly, the plasma catalyst may have an additional cap (601) and coating (607) on the wafer (602).
[0114] Figure 7The forms and materials of nanoporous wafers (602) and coatings (607) are presented. The wafers contain pores with openings on one or both sides; in the first case, the wafer has a so-called residual bed, which is retained after electrochemical processing of the original wafer material. Furthermore, the wafers may have cylindrical or V-shaped pores and an additional one-sided coating. The wafers are valve metal oxides, or silicon / silicon dioxide, or silicon carbide ceramics, synthesized by the following formula:
[0115] (Me 4 ) I (Me 5 ) J (Me 6 ) K (Me 13 ) L (Si) M (SiC) N (O) Z ,
[0116] Among them Me XX It is the valve metal of the IUPAC group XX transition metals; the subscript index is the numerical proportion of each type of atom; and one of I, J, K, L, M and Z is greater than 0, otherwise N = 1.
[0117] The chip (602) without the top cover (601) is synthesized according to the following formula:
[0118] (Me 4 ) I (Me 5 ) J (Me 6 ) K (Me 13 ) L (Si) M (O) Z ,
[0119] Among them, one of I, J, K, L, M, and Z is greater than 0.
[0120] It is also a heterogeneous redox catalyst, such as γ-Al₂O₃. The wafers can be synthesized according to custom formulas as needed.
[0121] The wafer coating (607) is a multilayer coating that does not include or includes any residual bed, and / or several thin films of a compound according to the following formula:
[0122] (Me 3 ) I (Me 4 ) J (Me 5 ) K (Me 6) L (Me 10 ) M (Me 11 ) N (O) Z ,
[0123] Among them, at least one of I, J, K, L, M, N and Z is greater than 0.
[0124] The nanowhisker family (604), (605) and (606) plays a major role in the absorption of UV-VIS-IR irradiation, thermoelectrically generating electricity and converting it into VUV-soft X-ray ionizing radiation through internal field-enhanced emission and electron scattering.
[0125] Figure 8 A family of nanowhiskers deposited within pores of a wafer (702) is depicted, including at least one of cylindrical or V-shaped nanowhiskers:
[0126] -Nano whiskers (604) are at least one of perovskite whiskers or conductive whiskers;
[0127] - Nano whiskers (605) are composite materials including perovskite-like whiskers and conductive whiskers.
[0128] - Nano whiskers (606) are composite materials comprising perovskite-like whiskers and conductive whiskers on both sides.
[0129] Perovskite-like nanocrystals have uniform or non-uniform crystalline structures and exist in polycrystalline or single-crystal forms synthesized according to the following general formula:
[0130] ∑[(Me 1-2 ) I (Me 1-2 ) J ](Me 3 ) K ∑[(Me 4-6 ) L (Me 4-6,8 ) M ]∑[(Me 4-6 ) N (Me 12-15 ) R ](sMe 13-16 ) X (nMe 14-16 ) Y (O) Z ,
[0131] The superscript index indicates the IUPAC group; the subscript index indicates the numerical proportion of each type of atom.
[0132] ∑[…] represents the (possible) formation of a complex of several elements from one or more groups including the superscript index;
[0133] Me, sMe, and nMe represent metal, metalloid, and nonmetal, respectively; and at least one of I, J, L, and Z is greater than 0 (e.g., LiNbO3 – perovskite-like lattice, homogeneous, single crystal), typically 0 ≤ I, J, K, L, M, N, R, X, Y, Z ≤ 30, for example, sodium barium niobate Ba2NaNb5O 15 Perovskite-like crystals.
[0134] Conductive nanocrystal materials are at least one of transition metals, metal-oxide-metal (MOM) or so-called transparent conductive oxide (TCO) ceramics that have low resistance at temperatures of several hundred degrees Celsius.
[0135] Figure 9 The top cover (601), its structure, and materials are described. In the case of using the top cover, according to... Figure 9 a. It should be transparent within the wavelength range and can be in the form of a thin film coating or a wafer.
[0136] The top cover (601) as a thin film coating includes at least a catalyst mesh layer (901), a layer for preventing oxidation and alkalinity (902), and a TCO ceramic layer (903).
[0137] According to the following general formula, the catalyst mesh layer (901) is at least one of a transition metal thin film or a MOM thin film:
[0138] (Me 3 ) I (Me 4 ) J (Me 5 ) K (Me 6 ) L (Me 10 ) M (Me 11 ) N (O) Z ,
[0139] Among them, at least one of I, J, K, L, M, N and Z is greater than 0.
[0140] When the top cover (601) is a Si wafer (904), it includes at least the following layers: a catalyst mesh layer (901); a layer (902) to prevent oxidation and alkalinity; and a TCO ceramic layer (903).
[0141] Figure 10A wafer bonding technique and the materials used for encapsulating plasma catalysts are described. In cases where the plasma catalyst comprises several wafers, encapsulation can be performed in one of the following ways:
[0142] - Adhesive bonding Figure 10 a;
[0143] - Glass slurry bonding Figure 10 b.
[0144] Adhesive bonding technology is based on the application of a specific mixture (1001) of inorganic binder and filler, which is selected taking into account the following parameters of the wafer (601, 602) and the calcined adhesive (1002):
[0145] - The difference in the coefficient of thermal expansion (CTE) of all materials used shall not exceed ±5%;
[0146] - The operating temperature and bonding pressure should not cause damage to any plasma catalyst components; and
[0147] - Electrical conductivity.
[0148] Glass paste bonding technology is based on the use of an organic binder, glass powder, and a specific mixture (1003) of conductive filler if required, which is selected taking into account the following parameters of the wafer (601, 602) and the glass (1004):
[0149] - The difference in the coefficient of thermal expansion (CTE) of all materials used shall not exceed ±5%;
[0150] - The operating temperature and bonding pressure should not cause damage to any plasma catalyst components; and
[0151] - Electrical conductivity.
[0152] The plasma catalyst in the form of a ceramic-matrix nanocomposite is a sintered solid thin ceramic brick in which there are no moving parts, it is self-powered and inherently reliable.
[0153] The plasma catalyst is placed inside the combustion chamber as a lining and can also act as a thermal barrier for the chamber walls.
[0154] It will be apparent to those skilled in the art that the present invention is not limited to the embodiments depicted in the drawings and described above, but that many other embodiments are possible within the scope of the appended claims.
Claims
1. A plasma catalyst in the form of a ceramic-matrix nanocomposite for initiating and sustaining plasma-assisted combustion, the nanocomposite being a structure comprising at least a first portion and a second portion, wherein: - the first part comprises a nanoporous wafer, and - the second portion comprises crystalline nanowhiskers, and - the nanowhiskers are deposited in the pores of the nanoporous wafer, - the nanoporous wafer comprises metal oxides of IUPAC Group 4 Ti, Zr, Hf, Group 5 V, Nb, Ta, Group 6 W and Group 13 Al of the periodic table, at least one of silicon / silicon dioxide and silicon carbide, and - said nanowhiskers having a diameter of 1 to 100 nm and an aspect ratio exceeding 100 comprise at least one of a perovskite-like polycrystalline and / or single crystal ferroelectric, a transition metal, a conductive metal-oxide-cermet or a composite thereof having thermoelectric properties, wherein said aspect ratio is length to diameter, wherein said nanowhiskers are capable of thermoelectrically generating electricity, converting the electricity into vacuum ultraviolet-soft X-ray ionizing radiation by internal field enhanced emission and electron scattering, - wherein the first and second parts are covered by an upper cover in the form of a multilayer film or wafer, -Wherein the upper cover comprises at least three layers: - Catalyst grid; - a layer to prevent oxidation and alkalinity; and - Transparent conductive oxide ceramic layer.
2. The plasma catalyst of claim 1, wherein the nanocomposite material is in the form of a sintered solid thin ceramic brick.
3. The plasma catalyst according to claim 1 or 2, wherein the nanoporous wafer of the first portion is in the form of a plane-parallel wafer comprising an array of self-organized, honeycomb-like and nearly monodisperse holes in cylindrical or V-shaped groups, which are open on both sides or only on one side and oriented perpendicular to the upper / bottom surface of the wafer.
4. The plasma catalyst of claim 1, wherein the nanoporous wafer is a ceramic synthesized according to the following formula: (Along with 4 ) I (Along with 5 ) J (Along with 6 ) K (Along with 13 ) L (si) M (SiC) N (of) Z , Among themMe 4 is a valve metal of the IUPAC Group 4 transition metal of the periodic table selected from the group consisting of Ti, Zr, Hf, Among themMe 5 is a valve metal of the IUPAC Group 5 transition metal of the periodic table, selected from the group consisting of V, Nb, Ta, Among themMe 6 is a valve metal of the IUPAC Group 6 transition metal of the periodic table, selected from the group comprising W, Among themMe 13 is Al, and where the indices I, J, K, L, M, N and Z are the numerical proportions of each type of atom; and one of I, J, K, L, M and Z is greater than 0, otherwise N=1.
5. The plasma catalyst according to claim 1, wherein the ferroelectric with thermoelectric properties is a perovskite-like crystalline nanowhisker in a polycrystalline or single crystal form, synthesized according to the following formula: ∑[(Me 1-2 ) I (Me 1-2 ) J ](Me 3 ) K ∑[(Me 4-6 ) L (Me 4-6,8 ) M ]∑[(Me 4-6 ) N (Me 12-15 ) R ](sMe 13-16 ) X (nMe 14-16 ) Y (O) Z , The superscript indices indicate the IUPAC groups of the periodic table. The subscript indices I, J, K, L, M, N, R, X, Y, and Z represent the numerical proportion of each type of atom. where ∑[…] denotes the formation of a complex of several elements of one or more groups including the superscript index, Where Me, sMe, and nMe represent metal, metalloid, and nonmetal, respectively, and At least one of I, J, L, and Z is greater than 0.
6. The plasma catalyst according to claim 5, wherein 0≤I, J, K, L, M, N, R, X, Y, Z≤30.
7. Use of the plasma catalyst according to any one of claims 1 to 6 as a component of a lining of a combustion chamber, said lining acting as an additional barrier against heat, oxidation and alkalinity for the combustion chamber wall.
